2004
DOI: 10.1530/eje.0.1510787
|View full text |Cite
|
Sign up to set email alerts
|

Novel ghrelin analogs with improved affinity for the GH secretagogue receptor stimulate GH and prolactin release from human pituitary cells

Abstract: Objective: Ghrelin, a recently identified 28-amino acid peptide is a potent GH secretagogue (GHS) produced predominantly by the stomach. Ghrelin stimulates GH secretion through binding to the GHS receptor in the hypothalamus and pituitary. In addition to the GH-releasing action, ghrelin has been found to be a powerful orexigenic factor. To assess the direct in vitro effects of ghrelin on human pituitary hormone secretion we have produced a panel of novel ghrelin analogs (molecular weight, 3323 -3384; human nat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 49 publications
(43 reference statements)
4
16
0
Order By: Relevance
“…Surprisingly, a previous study showed that ghrelin mRNA levels in somatotropinomas were negatively correlated with tumor size and, indeed, high-grade tumors had lower levels of ghrelin mRNA than low-grade adenomas (Kim et al 2001). On the other hand, both GHSR1a and GHSR1b have been found to be highly expressed in somatotropinomas compared with NPs (Barlier et al 1999, Korbonits et al 2001, Rubinfeld et al 2004, which together with the previous data mentioned in this section, might suggest the existence of an autocrine/paracrine role of the ghrelin system in GHproducing adenomas. Moreover, studies in a rat pituitary somatotrope cell line indicate that both AG and UAG can stimulate cell proliferation (Nanzer et al 2004).…”
Section: Endocrine-related Tumorsmentioning
confidence: 89%
See 2 more Smart Citations
“…Surprisingly, a previous study showed that ghrelin mRNA levels in somatotropinomas were negatively correlated with tumor size and, indeed, high-grade tumors had lower levels of ghrelin mRNA than low-grade adenomas (Kim et al 2001). On the other hand, both GHSR1a and GHSR1b have been found to be highly expressed in somatotropinomas compared with NPs (Barlier et al 1999, Korbonits et al 2001, Rubinfeld et al 2004, which together with the previous data mentioned in this section, might suggest the existence of an autocrine/paracrine role of the ghrelin system in GHproducing adenomas. Moreover, studies in a rat pituitary somatotrope cell line indicate that both AG and UAG can stimulate cell proliferation (Nanzer et al 2004).…”
Section: Endocrine-related Tumorsmentioning
confidence: 89%
“…Although the presence of ghrelin and its receptor has been confirmed in prolactinomas (Kim et al 2001, Korbonits et al 2001, Rotondo et al 2011, limited studies have been carried out to elucidate the direct pathological role of the ghrelin system in these tumors. Specifically, a previous study revealed that AG treatment elicited PRL release in prolactinomas and GH-PRL mixed adenoma cell cultures (Rubinfeld et al 2004), suggesting an involvement of the ghrelin system in the development and progression of prolactinomas. However, to the best of our knowledge, the role of other ghrelin gene-derived peptides, such as UAG or obestatin, on prolactinomas has not been explored so far.…”
Section: Endocrine-related Tumorsmentioning
confidence: 93%
See 1 more Smart Citation
“…Indeed, ghrelin has been reported to stimulate PRL synthesis and secretion both in animals (Kaiya et al, 2003;Riley et al, 2002) and in humans (Arvat et al, 2001;Baldelli et al, 2004;Broglio et al, 2003;Rubinfeld et al, 2004). It is also possible that ghrelin inhibits the increase in lactotroph cell death seen in poorly controlled diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with observations that ghrelin affects synaptogenesis and development of neuronal circuits, as well as modulation of memory processes, sleep patterns and behavior [44,45,46,47,48,49,94,95,96]. Within the hypothalamus-pituitary axis, GHS-R1a mediates ghrelin/GHS modulation of GH, PRL, CRH/ACTH and GnRH/gonadotropin secretion [26,27,28,97,98,99,100,101,102]. Orexigenic effects of ghrelin/GHS are likely mediated by GHS-R1a expressed by hypothalamic neurons containing neuropeptide Y (NPY)/Agouti-related protein [34,103,104,105,106].…”
Section: Type 1a Ghs Receptormentioning
confidence: 99%